Design and development of nanoprobes radiolabelled with 99mTc for the diagnosis and monitoring of therapeutic interventions in oncology preclinical research - Salgueiro, Maria Jimena (2024)
Fil: Salgueiro, Maria Jimena. Universidad de Buenos Aires; Argentina